Avaliação do crescimento de mudas de bananeira CV. Prata anã, com adubação mineral e orgânica - Santos, Ailton Mascarenhas dos (2012)
Brazil is the fourth largest producer of banana with 12.74% of production. The Northeast region has excellent climate and soil conditions to produce fruit of high quality, but there are several problems affecting the banana crop in the region, resulting in low productivity and quality. In this context the use of liquid biofertilizers stands out for having great acting and microbial activity in nutrient cycling, promoting the improvement in physical, chemical and biological soil properties. In order to evaluate the effect of a liquid biofertilizer on the growth of banana, an experiment was conducted in pots with a capacity of 4,5 kg soil in a greenhouse. It was used two doses of mineral fertilizer (0 and 100 ml of nutrient solution/pot/week), three doses of banana crop residues (0, 50 and 100 g of dry matter /pot 4,5 Kg) and three doses of biofertilizer (0 , 100 and 200 ml/pot/week from an extract prepared from an organic compound inoculated with EM-4®), disposed factor (2x3x3), with 18 treatments with 5 replications (90 experimental units), conducted in a split completely randomized experimental, plant response were micropropagated banana plantlets cv. Prata-Anã. The location of the development of research belongs to the area of the Centro de Ciências Agrárias da Universidade Federal do Ceará, campus Pici, Fortaleza – CE. We used a soil surface layer (0-20 cm) of a Cambissolo Háplico Tb Eutrófico from Chapada do Apodí – CE. The experiment was conducted for a period of 94 days, after the last addition of liquid bio-fertilizer and mineral fertilizer, the plants were harvested and separated into shoots and roots for dry matter determination and analysis of total nutrients. The mineral fertilizer and biofertilizer contributed to plant growth and nutrient uptake, contrary to what occurred to the crop residue.